Edukasi dan Skrining Kesehatan bagi Lansia untuk Pencegahan Komplikasi Penyakit Kronis - Siti Latipah; Naryati Naryati; Giri Widakdo; Nurenah Nurenah; Hafizhah Diyanah Zhafirah; Nabillah Hassanah; Muhammad Fakhrian Saputra (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
The community service activity entitled “Healthy Living in Facing Chronic Diseases in Elderly: Towards Healthy and Active Elderly” was conducted at Posyandu Lansia Cendana, RW 04, Sumur Batu Village, Kemayoran, Central Jakarta. This program aimed to enhance the knowledge and awareness of elderly individuals regarding chronic disease management through structured health education and basic health screening. The activity employed a participatory and educational approach, including interactive counseling, healthy lifestyle training, elderly exercise sessions, and simple health assessments (blood pressure, random blood glucose, body mass index, and waist circumference). A total of 100 elderly participants took part, supported by healthcare professionals, local cadres, and community leaders. The results showed that most participants were women (87%) aged between 61 and 79 years. Screening data revealed that the majority of participants had a body mass index in the overweight category (48%) and waist circumference above the normal limit, indicating a high risk of metabolic disorders. Moreover, random blood glucose results suggested that many participants were in the prediabetic range. Statistical analysis demonstrated a significant improvement in knowledge scores before and after the educational intervention (p = 0.014), indicating the effectiveness of the program in improving elderly participants’ understanding of chronic disease prevention and management. This activity proved effective in promoting awareness, healthy lifestyle adoption, and early detection of chronic disease complications among the elderly. Furthermore, it positively influenced psychosocial well-being by enhancing confidence and social engagement. It is recommended that similar programs be conducted regularly and integrated into community-based elderly health initiatives, such as Posyandu Lansia, with active involvement of local health cadres to ensure program sustainability.